2010
DOI: 10.2466/pr0.106.2.323-341
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Validity of the Academic Motivation scale with a United States Business Student Sample

Abstract: This study examined alternative seven-, five-, and three-factor structures for the Academic Motivation Scale, with data from a large convenience sample of 2,078 students matriculating in various business courses at three AACSB-accredited regional comprehensive universities. In addition, the invariance of the scale's factor structure between male and female students and between undergraduate and Master's of Business Administration students was investigated. Finally, the internal consistency of the items loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
3
25
1
5
Order By: Relevance
“…Finally, gender invariance was assessed. Previous studies indicated various levels of gender invariance (e.g., Guay et al, 2015;Smith et al, 2010). Our results reinforce these and give strong support for the complete invariance of male-female groups on the level of latent mean invariance, further enhancing the cross-gender generalizability of the AMS.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, gender invariance was assessed. Previous studies indicated various levels of gender invariance (e.g., Guay et al, 2015;Smith et al, 2010). Our results reinforce these and give strong support for the complete invariance of male-female groups on the level of latent mean invariance, further enhancing the cross-gender generalizability of the AMS.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, latent variancescovariances and latent means can also be investigated. Multiple invariance tests were carried out on AMS by comparing groups based on gender, types of high school, academic years, or the abilities of students (e.g., Alivernini & Lucidi, 2008;Caleon et al, 2015;Guay et al, 2015;Smith et al, 2010). The present study intends to test the replicability of these results and include further subgroups in the analyses as well by comparing Eastern European and Western European contexts.…”
Section: Measurement Invariance For Group Differencesmentioning
confidence: 99%
“…Normalmente, as pesquisas sobre motivação são realizadas utilizando instrumentos de auto-relato [18,23,[26][27][28]. Surge, com isso, uma preocupação quanto aos instrumentos de avaliação utilizados com essa população, pois, em sua maioria, são provenientes de estudos locais ou regionais [2,22,25,29,30], o que gera a necessidade de serem mais bem investigados, sobretudo no que se refere à validação para a realidade brasileira [31,32].…”
Section: Introductionunclassified
“…Corroborando tal afirmativa, Smith et al (2010, p.323) e Hegarty (2010 afirmam que, mesmo depois de décadas, os pesquisadores ainda apresentam grande interesse na relação entre motivação e resultados educacionais.…”
Section: Motivação Acadêmicaunclassified
“…Tais resultados foram ao encontro dos encontrados por Smith et al (2010), tendo em vista que todas as correlações apresentaram-se significantes, ao menos com 5%, exceto as correlações existentes entre as dimensões MECE / MIVE e DESM / MEIN.…”
Section: Estudo Descritivo Da Emaunclassified